Epistemologi Ilmu Perspektif Islam (Studi Kritis Atas Positivisme, Pospositivisme, Teori Kritis, dan Konstruktivisme) - Deni Solehudin; Nanat Fatah Natsir; Erni Haryanti (Jurnal Ilmiah Wahana Pendidikan, 2021)
There are three big problems that have long been the object of human thought, namely about humans themselves, nature, and God. Humans with all the potential that exists in themselves are always looking for the essence of themselves, the natural surroundings, including humans other than themselves, and the supernatural powers they feel. So they always look for the truth behind it. Through deep reflection, branches of the philosophy of science were born, including Positivism, Pospositivism, Critical Theory, and Constructivism. The research method used is literature study. The results of the study show that the source of human knowledge is man himself, the natural surroundings and God. The tools to reach it have been provided by Allah SWT. As informed in the Qur'an. However, the reach of the human mind is limited, there are transcendental things (including God) that cannot be reached by a mere mind. To reach this problem, humans have been given various tools to achieve it, namely the mind, heart, fuad, and the five senses.